2015
DOI: 10.3892/or.2015.4218
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LPS-induced epithelial-mesenchymal transition by aqueous extracts of Prunella vulgaris through inhibition of the NF-κB/Snail signaling pathway and regulation of EMT-related protein expression

Abstract: Epithelial-mesenchymal transition (EMT) is a pivotal event in the invasion and metastasis of cancer cells. Prunella vulgaris (PV) inhibits the proliferation of various cancer cells; however, its possible role in EMT has not been demonstrated. In the present study, we explored the effect of PV aqueous extract (PVAE), a typical medicine for decoction, on EMT. Lipopolysaccharide (LPS) induced EMT-like phenotype changes in cancer cell lines that enhanced cell migration and invasion. PVAE markedly inhibited these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We found that the overall variance was higher in treated cells versus untreated cells with an accompanying increase in the mean duration 23.7±4.73 and 21.7±3.42 hours, respectively (Figure 4a). Additionally, we also found that the addition of LPS appeared to enhance cell motility, as LPS treated cells showed an increase in overall cell displacement (Supplementary Figure 5), which supports the notion that LPS can induce epithelial-mesenchymal transition via TLR4 signaling [26][27][28] .…”
Section: Impact Of Lps On Cell Cycle Duration Variabilitysupporting
confidence: 79%
“…We found that the overall variance was higher in treated cells versus untreated cells with an accompanying increase in the mean duration 23.7±4.73 and 21.7±3.42 hours, respectively (Figure 4a). Additionally, we also found that the addition of LPS appeared to enhance cell motility, as LPS treated cells showed an increase in overall cell displacement (Supplementary Figure 5), which supports the notion that LPS can induce epithelial-mesenchymal transition via TLR4 signaling [26][27][28] .…”
Section: Impact Of Lps On Cell Cycle Duration Variabilitysupporting
confidence: 79%
“…37 The exposure to LPS may induce tumor proliferation and facilitate invasion. 29,30,32 For example, Wang et al reported that hepatocellular cancer cell survival and proliferation were enhanced upon LPS stimulation. 38 Similarly, Yang et al demonstrated that LPS could induce cell proliferation in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is known as an inducer of cell proliferation and invasion in various cancers. 29,30 Therefore, we examined the effect of MRPS23 down-regulation on LPS-induced proliferation and invasion of OS cells. The MTT and transwell assays were performed to measure cell proliferation and invasion, respectively.…”
Section: Down-regulation Of Mrps23 Induces Loss Of Mitochondrial Membmentioning
confidence: 99%
“…Strikingly, PV annulled such inflammatory responses induced by dsDNA or dsRNA in thyrocytes, and provided an exceptional protective effect in the immune-activated thyrocytes. Such antiinflammatory action of PV in thyrocytes, in addition to its previously documented immunomodulatory effects in macrophages (26,27,29), may help to explain the observed therapeutic efficacy of PV for Hashimoto's thyroiditis. In turn, our new findings highlight that innate immune responses in thyrocytes triggered by dsDNA or dsRNA is likely a critical factor for precipitating thyroid autoimmunity, and herbal/ compound agents (i.e.…”
Section: Discussionmentioning
confidence: 81%